Degradabilidade e digestibilidade de híbridos de milho em função do estádio de colheita, tamanho de partícula e processamento por meio do esmagamento na ensilagem - Factori, Marco Aurélio [UNESP]; Costa, Ciniro [UNESP]; Meirelles, Paulo Roberto de Lima [UNESP]; Da Silva, Marina Gabriela Berchiol [UNESP]; Da Silveira, Joao Paulo Franco [UNESP] (My University, 2014)
During the process of silage corn, should take into consideration some aspects that will result in better utilization. The aim of this study was to evaluate the degradability of dry matter (DM), crude protein (CP), neutral detergent fiber (NDF) and starch digestibility and in vitro dry matter (DM) of silage corn hybrids due two textures, three stages of harvest, three particle sizes and processing by crushing. After harvesting and chipping, part of the material was crushed and then ensiled and sealed for 45 days. After opening the silos, analyzed the degradability in the incubation time of 20 hours using the technique in situ macro bag. The experimental design was a randomized split plot. The DM degradability was influenced only by the effect of stages of sampling used. The degradability of CP showed interaction between processing and particle size (Tp), noting that increased degradation due to processing. For NDF degradation significant interaction of factors, hybrid and processing, similar to the degradation of starch. The IVDMD was influenced by the effects of hybrid, stadium, Tp and processing. It can be concluded that benefits were higher with the use of processing associated with more advanced stages of harvest, in larger particle sizes.
Degradability and digestibility of corn hybrids as a function of harvesting stage, particle size and processing through the crushing of silage
Keywords: Hard texture; Macro bag; Silage; Soft texture